The black box of revolution ―"A Captive in Love", by Jean Genet: reading notes― - Casado, Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper analyzes the latest work by Jean Genet, A Captive in Love, in which the French author recounts his stay in Jordan and Palestine as a witness to an exceptional historical moment. The proposal of a shared subjectivity, in addition to an ethical and political position that does not shy away from aesthetic stimuli, led him to create his own poetic language with which to describe the revolutionary processes of those difficult years.